PECULIARITIES OF GROUNDWATER OCCURRENCE AND SAFE YIELD ESTIMATION IN THE TERRITORY OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2012)
The article presents the classification of fresh groundwater deposits of commercial importance of their occurrence in the territory of Armenia. The following types of fresh groundwater deposits have been distinguished: 1) water-table aquifers of narrow river valleys; 2) fracture waters of volcanic rocks; 3) confined-nonconfined waters of intermountain basins. Natural and artificial resources and reserves occur in these types of deposits as well as attracted groundwater resources. They provide operational reserves of groundwater. The estimation of safe yield out of fresh groundwater resources and reserves is provided.
Keywords: spring catchment; borehole; resource utilization factor; hydraulic interaction